Answer:
The equation of the line is;
![y=-(1)/(3)x-3](https://img.qammunity.org/2023/formulas/mathematics/college/u3mhufhrmei4zd86qusj375wk1xfazayjb.png)
Step-by-step explanation:
Given that;
The line has the same slope as ;
![y=-(1)/(3)x+4](https://img.qammunity.org/2023/formulas/mathematics/college/gse9nrgil9ud8varl4j2x9arhu0byawk19.png)
Compare to the standard slope intercept equation of a straight line;
![y=mx+b](https://img.qammunity.org/2023/formulas/mathematics/high-school/smsb8cbft03lwblmi49nf2l6jby2ofxzws.png)
The slope m of the line is;
![m=-(1)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/vy64mdjniypv9sfu22874ekdqjkryr3ckz.png)
Given that the line passes through point;
![(6,-5)](https://img.qammunity.org/2023/formulas/mathematics/college/52mu3wfyna1hdhs4okz6g1s0b7wrckwlme.png)
let us derive its equation by using the point slope equation of line;
![\begin{gathered} y-y_1=m(x-x_1)_{} \\ \text{substituting the slope and the given point, we have;} \\ y-(-5)=-(1)/(3)(x-6) \\ y+5=-(1)/(3)x+(6)/(3) \\ y+5=-(1)/(3)x+2 \\ y=-(1)/(3)x+2-5 \\ y=-(1)/(3)x-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bejfaxn6tnoj6yys4d0lti6qo6slh65je3.png)
Therefore, the equation of the line is;
![y=-(1)/(3)x-3](https://img.qammunity.org/2023/formulas/mathematics/college/u3mhufhrmei4zd86qusj375wk1xfazayjb.png)